Performance evaluation of SEPIC, Luo and ZETA converter - Niranjana Siddharthan; Baskaran Balasubramanian (Institute of Advanced Engineering and Science, 2019)
DC-DC converters are devices which convert direct current (DC) from one voltage level to another by changing the duty cycle of the main switches in the circuits. These converters are widely used in switched mode power supplies and it is important to supply a constant output voltage, regardless of disturbances on the input voltage. In this work, the performance of three different converters such as Single-Ended Primary-Inductance Converter (SEPIC), Luo converter and ZETA converter have been analyzed. Further, the parameters values such as ripple voltage, switching losses and efficiency of the proposed three different converters were compared with each other. Also, the simulation work has been carried out using MATLAB/SIMULINK software. From the comparison of obtained results, it is observed that the ZETA converter has high significance than the SEPIC and Luo converter.